2015
DOI: 10.1111/iwj.12421
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enzymatic debridement with two different collagenases versus mechanical debridement on chronic hard‐to‐heal wounds

Abstract: A chronic ulcer is usually defined as an injury that does not spontaneously evolve towards healing and does not progress through normal healing stages such as inflammation, proliferation and remodelling. This study was designed in order to compare two types of collagenases with mechanical debridement alone. It was thus possible to evaluate their differences in terms of pain and debridement efficacy. Patients were divided into three groups: 30 patients were daily dressed using an ointment based on collagenase p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 11 publications
2
26
0
Order By: Relevance
“…Numerous studies have been carried out on the combined use of NPWT over dermal substitutes also to cover large and deep wounds (including bone and tendon exposure) [7–13]. Every study assessed that, thanks to the integrated use of these techniques, the preparation of the wound bed was quicker in order to obtain a better graft take [14]. In fact NPWT used over the dermal template delivered a faster maturation (approximately 1-2 weeks) and a higher integration quality [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been carried out on the combined use of NPWT over dermal substitutes also to cover large and deep wounds (including bone and tendon exposure) [7–13]. Every study assessed that, thanks to the integrated use of these techniques, the preparation of the wound bed was quicker in order to obtain a better graft take [14]. In fact NPWT used over the dermal template delivered a faster maturation (approximately 1-2 weeks) and a higher integration quality [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…Further research into the efficacy of enzymatic debridement in small animal practice should include a comparison with different methods of debridement used in similar wounds, as carried out in human patients by O n e s t i et al [6]. Further research should also include histological analysis of the wound before and after enzymatic debridement.…”
Section: Methodsmentioning
confidence: 99%
“…Both studies found the treatment to be well-tolerated by patients and even to reduce pain at the wound site. Another human study by O n e s t i et al [6] compared the efficacy of enzymatic and mechanical debridement and showed that cases treated with enzymatic debridement had more rapid reduction in wound size and caused less pain than debridement using wet-to-dry dressings.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations